Visualisation of HER2 homodimers in single cells from HER2 overexpressing primary formalin fixed paraffin embedded tumour tissue - Diana B. Peckys; Daniela Hirsch; Timo Gaiser; Niels de Jonge (BMC, 2019)
Abstract Background HER2 is considered as one of the most important, predictive biomarkers in oncology. The diagnosis of HER2 positive cancer types such as breast- and gastric cancer is usually based on immunohistochemical HER2 staining of tumour tissue. However, the current immunohistochemical methods do not provide localized information about HER2's functional state. In order to generate signals leading to cell growth and proliferation, the receptor spontaneously forms homodimers, a process that can differ between individual cancer cells. Materials and methods HER2 overexpressing tumour cells were dissociated from formalin-fixed paraffin-embedded (FFPE) patient's biopsy sections, subjected to a heat-induced antigen retrieval procedure, and immobilized on microchips. HER2 was specifically labelled via a two-step protocol involving the incubation with an Affibody-biotin compound followed by the binding of a streptavidin coated quantum dot (QD) nanoparticle. Cells with membrane bound HER2 were identified using fluorescence microscopy, coated with graphene to preserve their hydrated state, and subsequently examined by scanning transmission electron microscopy (STEM) to obtain the locations at the single molecule level. Label position data was statistically analysed via the pair correlation function, yielding information about the presence of HER2 homodimers. Results Tumour cells from two biopsies, scored HER2 3+, and a HER2 negative control sample were examined. The specific labelling protocol was first tested for a sectioned tissue sample of HER2-overexpressing tumour. Subsequently, a protocol was optimized to study HER2 homodimerization in single cells dissociated from the tissue section. Electron microscopy data showed membrane bound HER2 in average densities of 201-689 proteins/μm2. An automated, statistical analysis of well over 200,000 of measured protein positions revealed the presence of HER2 homodimers in 33 and 55% of the analysed images for patient 1 and 2, respectively. Conclusions We introduced an electron microscopy method capable of measuring the positions of individually labelled HER2 proteins in patient tumour cells from which information about the functional status of the receptor was derived. This method could take HER2 testing a step further by examining HER2 homodimerization directly out of tumour tissue and may become important for adjusting a personalized antibody-based drug therapy.